The Dilemma of Post-Colonial Universities - Yann Lebeau, Mobolaji Ogunsanya (dir.) (IFRA-Nigeria, 2000)
The papers in this volume were presented at a conference organized by the Institut Français de Recherche en Afrique (IFRA) at the University of Ibadan on the 26th and 27th of October 1998, as part of the 50 anniversary celebrations of the University. This conference brought together scholars from anglophone and francophone countries who have been collaborating on a research programme which is concerned with elite formation and the restructuring of higher education in sub-Saharan Africa. The p...